2021
DOI: 10.1111/andr.13034
|View full text |Cite
|
Sign up to set email alerts
|

Growth, growth potential, and influences on adult height in the transgender and gender‐diverse population

Abstract: The sexually dimorphic trait of height is one aspect of the experience of transgender and gender-diverse (TGD) individuals that may influence their gender dysphoria and satisfaction with their transition. In this article, we have reviewed the current knowledge of the factors that contribute to one's final adult height and how it might be affected in TGD youth who have not experienced their gonadal puberty in the setting of receiving gonadotropin-releasing hormone analog (GnRHa) and gender-affirming hormonal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 115 publications
(311 reference statements)
0
6
0
Order By: Relevance
“…Concurrently, the number of youth presenting for transgender care is growing with a steadily increasing demand for services in multidisciplinary clinics on several continents ( 6 ). Methods for tracking growth parameters in this population are lacking, and while it has been proposed that such youth be dually-tracked on girl and boy growth charts, this approach has limitations (i.e., may misclassify diagnoses of weight-related disorders; lead to difficulties predicting near adult height) ( 7 , 10 , 44 ). Therefore, there is a need to track how one is growing as a “transgender child” compared to specifically as a “girl” or “boy.” Our growth charts and z-score calculators can serve as an intermediate reference between the male-specific or female-specific data points until longitudinal growth data are available for the creation of transgender-specific growth charts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, the number of youth presenting for transgender care is growing with a steadily increasing demand for services in multidisciplinary clinics on several continents ( 6 ). Methods for tracking growth parameters in this population are lacking, and while it has been proposed that such youth be dually-tracked on girl and boy growth charts, this approach has limitations (i.e., may misclassify diagnoses of weight-related disorders; lead to difficulties predicting near adult height) ( 7 , 10 , 44 ). Therefore, there is a need to track how one is growing as a “transgender child” compared to specifically as a “girl” or “boy.” Our growth charts and z-score calculators can serve as an intermediate reference between the male-specific or female-specific data points until longitudinal growth data are available for the creation of transgender-specific growth charts.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it may be helpful to have sex non-specific height velocity charts and z-score calculators given their importance and practicality for tracking changes in height over shorter time durations ( 49 ). This is especially important given that height velocity may be altered by GnRHa and/or cross-sex hormonal therapy use ( 44 , 50 ). Given the inherent limitations of creating height velocity charts using cross-sectional data, development of these charts would be best done using longitudinal cohorts and data registries tracking individuals’ growth over time ( 51 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Optimizing height in TGD young people is an area of active investigation, and the effects of GAH on height are unclear. Studies of transfeminine individuals have demonstrated that height obtainment is variable depending on the bone age of participants at the onset of therapy, the estrogen dose, and the type of estrogen used [39, 40]. High-dose oral estrogen therapy during adolescence has been suggested to reduce adult height in transfeminine individuals predicted to have an adult height far outside the typical female range.…”
Section: Outcomes Of Medical Gender-affirming Carementioning
confidence: 99%
“…Starting with TGD adolescents, Roberts and Carswell review how the treatment of TGD youth who have not experienced their gonadal puberty can affect their height, particularly in the setting of pubertal suppression with gonadotropin-releasing hormone analogues. 5 Quinn et al review the reproductive considerations for TGD adolescents and young adults. 6 They focus on reproductive health goals, sexual function, HIV/STI risk, barriers to accessing competent care, and how training programs can improve care.…”
Section: E D I T O R I a L The Growing And Interdisciplinary Field Of...mentioning
confidence: 99%
“…Starting with TGD adolescents, Roberts and Carswell review how the treatment of TGD youth who have not experienced their gonadal puberty can affect their height, particularly in the setting of pubertal suppression with gonadotropin‐releasing hormone analogues 5 . Quinn et al.…”
mentioning
confidence: 99%